A expressão no ciberespaço: um voltar-se fenomenologicamente para o diálogo acerca de conteúdos matemáticos - Ferreira, Miliam Juliana Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The improvement of the Technologies of Information and Communication (TIC) resulted in the creation of new ways people communicate and new spaces where this communication takes place. Considering a variety of new spaces, we decided to highlight, on this study, the Cyberspace. On social networks such as Facebook and Orkut, exit many groups and communities focused on discussion and conversation on different topics: from information to entertainment. On this dissertation, we report our experience wi th three virtual communities from Facebook and Orkut. Also, mathematics was the topic of discussion on each of the studied communities. Our goal was to understand, from a phenomenological perspective, how dialogues about mathematics content are possible and how they happen on those social network communities. In order to comprehend these dialogues, we studied the works of Merleau-Ponty. Also, the works of Bicudo and Rosa were extremely important for our understanding of cyberspace. In addition to our theoretical study, we followed two communities on Orkut and one on Facebook. Based on ways which members of these communities expressed themselves, we tried to analyze how dialogues about mathematics occur and what they reveal about math. The analyzes of our data, designed on phenomenological manner, allowed us to create four open-categories: listen the other, expression by speech, expression by image, and expression by the use of mathematical language. The interpretation of these categories presented to us how individuals talked about math on the cyberspace. We realized that the 'listen the other' is a started for communication. Complementarily, we noticed the intentional desire of individuals to be with others members of the community. On the dialogue, the 'be-with' shows itself by the speech. On the cyberspace, the 'be-with' is represented by the written text, image that speaks and by the oral expression

Com a chegada das Tecnologias de Informação e Comunicação (TIC) surgiram novos modos de os sujeitos se comunicarem e outros espaços comunicativos. Dentre tais espaços destaca-se, neste estudo, o ciberespaço. Nas Redes Sociais como o Facebook e o Orkut, existem comunidades/grupos em que os diálogos englobam temas que variam desde informação até entretenimento. Neste trabalho relatamos a experiência vivida em três comunidades virtuais das redes sociais Facebook e Orkut, nas quais os sujeitos discutem Matemática. Procuramos, nessas comunidades, compreender, numa perspecti va fenomenológica, ‘como o diálogo acerca do conteúdo matemático é possível e se dá em comunidade/grupos das Redes Sociais: Facebook e Orkut’. Para que pudéssemos compreender esse diálogo procuramos clareza em obras de Merleau-Ponty. Bicudo e Rosa também foram significativos para a compreensão do ciberespaço. Acompanhamos duas comunidades do Orkut e um grupo do Facebook, focando os modos de expressão dos participantes procuramos entender como o diálogo se dá e o que nele se revela acerca da matemática. A análise dos dados, desenvolvida numa postura fenomenológica, permitiu-nos a construção de quatro categorias abertas: o ouvir o outro, a expressão pela fala, a expressão por imagem e a expressão pela linguagem matemática. A interpretação de tais categorias vai mostrando os modos de os sujeitos se disporem a dialogar sobre conteúdos matemáticos no ciberespaço. Vimos que o ouvir o outro é o que abre à comunicação. Há uma intencionalidade dos sujeitos que os dispõem a estar uns com os outros. No estar-com o diálogo mostra-se na fala que no ciberespaço caracteriza-se pelo texto escrito, pela imagem que diz, pela oralidade
Keywords: Mathematics - Study and teaching; Matemática - Estudo e ensino; Ciberespaço; Fenomenologia; Tecnologias de informação e comunicação; Redes sociais